High occurrence of hepatitis E virus in raw pork liver and pork liver pâté produced in the Canadian province of Quebec - Chatonnat, Eva; Julien, Mariya; Jubinville, Eric; Goulet-Beaulieu, Valérie; Pavio, Nicole; Jean, Julie (Frontiers in Sustainable Food Systems, 2023)
Hepatitis E virus is widespread throughout the world and causes sporadic cases of liver disease. In industrialized countries its transmission is zoonotic, with pigs, deer and wild boar being major reservoirs. Humans can be infected by ingesting raw or undercooked contaminated meat products. In the Canadian province of Quebec, HEV has been detected previously in pork liver and chops. In the present study, we analyzed 83 pork liver pâtés sold in local grocery stores and in 79 raw pork livers obtained from Quebec hog processers. HEV RNA was extracted and detected by RT-qPCR. HEV RNA was amplified in 29% of the pâtés and in 4% of the raw pork livers. Out of all amplified PCR positive samples, only one showed a product during electrophoresis and was sent for sequencing. The resulting sequence matched a strain belonging to genotype 3 (HEV-3). This pilot study shows that HEV is present frequently in pork-liver-based products in the province of Quebec.